Exploring Influencers' Commercial Content on Instagram - Hogsnes, Mathilde; Grønli, Tor-Morten; Hansen, Kjeld (Journal of interactive advertising, 2024)
This study, which explored how commercial products and services are displayed by different influencer categories on Instagram, was motivated by the need for a more transparent picture of the commercial content consumed by followers. Drawing from an ethnographic content analysis of 3,278 Instagram posts, we found that social media influencers with a minor following had a higher number and a broader variety of commercial posts. Additionally, products and services were displayed through subtle patterns, often integrated into the influencers' lifestyles and social activities. Although social media influencers with many followers had fewer commercial posts, their display of products and services was more direct and informative. The study closes a literature gap by providing a more refined understanding of social media influencers' commercial content on Instagram. It offers managerial implications based on the societal impact of the commercial content that people consume.